Knowledge, attitude and preventive practices of hepatitis B infection among health trainees, northern region of Ghana - Cudjoe, Francis Kronzu; Abdulai, Tanko; Mohammed, Abdul-Samed; Twiaku, Sophia; Amoakoh, Michael Yaw (International Journal Of Community Medicine And Public Health, 2026)
Background: Hepatitis B virus (HBV) infection remains a major global health challenge, causing chronic liver diseases such as cirrhosis and hepatocellular carcinoma. Despite the availability of a safe and effective vaccine, infection rates remain high, particularly among healthcare workers and trainees. This study assessed the knowledge, attitude, and preventive practices regarding hepatitis B infection among health trainees at the University for Development Studies (UDS), Tamale, Ghana. Methods: A cross-sectional study was conducted among 400 health trainees selected through stratified random sampling from six schools and faculties within the UDS Dungu Campus. Data were collected using a structured questionnaire and analysed with SPSS version 23. Descriptive statistics summarized participants’ characteristics, while Chi-square and multivariable logistic regression identified factors associated with preventive practices. Statistical significance was set at p<0.05. Results: Overall, 58.3% of participants demonstrated good knowledge of hepatitis B. Most participants (70.5%) had positive attitudes, and 70% exhibited good preventive practices. 61% of participants had received at least a dose of Hepatitis B vaccine, though only 10.5% completed post-vaccination antibody testing. Good attitude significantly predicted good practice (AOR=4.495, 95% CI: 2.613-7.731, p<0.001). Female students were more than twice likely to practice prevention (AOR=2.212, 95% CI: 1.262-3.877, p=0.006). Conclusions: Health trainees demonstrated moderate knowledge and generally positive attitudes toward hepatitis B prevention. However, gaps in screening, post-vaccination testing, and exposure reporting indicate the need for strengthened health education and institutional vaccination programmes in Ghana.